Penggunaan Bobot Potong dan Bobot Karkas sebagai Penduga Yield Grade dan Luas Urat Daging Mata Rusuk Kambing Kacang - Pradana, Erbid Dwi; Muthalib, R. A.; Farizal, Farizal; Afzalani, Afzalani; Sulaksana, Indra; Hoesni, Fachroerrozi (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the shape and closeness of the relationship between slaughter weight and carcass weight with yield grade and rib eye muscle area in kacang goats. The material used in the research was 30 male kacang goats at the Mat Beken livestock business with 15 age groups I2 (2 -2,5years), and 15 I3 (3 -3,5 years). The tools used are knives, machetes, ropes,